2012
DOI: 10.1007/s10661-012-2730-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals and their interrelationships with some physicochemical parameters in eco-efficient rivers of Himalayan region

Abstract: Most precious and world famed Himalayan rivers like Ganga, Yamuna, and their tributaries are originated from Uttarakhand state of India. Over the years, increased industrial activities and urban growth along the rivers and lakes have resulted in increased load over the water bodies. In the present study, a comparison of characteristics of water quality with respect to heavy metals (Fe, Zn, Cu, and Pb) and their interrelationships with some physiological parameters during different seasons of year 2010 has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The concentration of the lead was found to be 2 to 16 times higher comparing to its desirable limit (0.05mg/L) except site HK1 where lead was within a range. One of the major sources of lead is industrial effluent discharged in river water without any prior treatment or improper treatment [28]. The high concentration of lead in river water can damage the central nervous system, kidneys and blood system [29].…”
Section: Heavy Metalsmentioning
confidence: 99%
“…The concentration of the lead was found to be 2 to 16 times higher comparing to its desirable limit (0.05mg/L) except site HK1 where lead was within a range. One of the major sources of lead is industrial effluent discharged in river water without any prior treatment or improper treatment [28]. The high concentration of lead in river water can damage the central nervous system, kidneys and blood system [29].…”
Section: Heavy Metalsmentioning
confidence: 99%
“…0.3 mg/l. In POM season, water samples of all the rivers were found within limits but in earlier investigation, Kansal et al (2013) also reported the higher iron concentration in river water samples of Uttarakhand.…”
Section: Resultsmentioning
confidence: 64%
“…On the contrary, higher metal concentrations observed during the monsoon season at few locations might be due to the mixing of more polluted water with less contaminated water during the rainy season. This might be contributed by the sewage overflows and runoff from agricultural and dumping sites wastes in the vicinity [37].…”
Section: Heavy Metals Concentrationsmentioning
confidence: 99%